Dislocated posterior chamber intraocular lens (PCIOL) in patients with retinitis pigmentosa (RP) - Lam, CS; Mae-Lynn Catherine Bastion (Pusat Perubatan Universiti Kebangsaan Malaysia, 2017)
Subluxation or dislocation of PCIOL is one of the complications of cataract operation in RP patients. This paper reports the presentation of PCIOL dislocation and subluxation and the management and outcome in 3 eyes of 2 RP patients. Two medical records of patients with RP who developed dislocated or subluxated PCIOL and subsequently underwent explantation of the dropped IOL were evaluated. Two patients had bilateral eye cataract operation done and had PCIOL implanted. Patient 1 developed left eye subluxated PCIOL inferiorly after 2 years of the cataract operation and right eye dislocated PCIOL anteriorly 4 years after cataract operation. Patient 2 develop right eye subluxated PCIOL inferiorly after 12 years of the cataract operation. Patient 1 with right eye dislocated PCIOL underwent intraocular lens (IOL) explantation and was left aphakic as her visual prognosis was poor due to advanced RP. The left IOL remained within the visual axis despite subluxation and no intervention has been done. Patient 2 with right eye subluxated PCIOL underwent IOL explantation and anterior chamber intraocular lens (ACIOL) implantation. ACIOL remained stable and visual acuity improved post-operation. Both the operations were uneventful. Post-operatively, there was no elevated intraocular pressure and no prolonged ocular inflammation, which required prolonged anti-inflammatory and no retinal detachment was seen. Both patient and surgeon should be aware of potential PCIOL subluxation or dislocation in RP. The presentation may be as late as more than a decade after the cataract operation.